Pengaruh Publicnes Terhadap Hubungan Antara Partisipasi Pembuatan Anggaran Dengan Kinerja Manajerial - Alliyah, Siti (potensio, 2008)
This study aims to examine the relationship between participation in budget making and managing performance. Results obtained from these studies have been done was not consistent and there was a contradiction between one researcher to another. This study provides empirical evidence about the effect of publicness on the relation between participation in budget making and managing performance in Universities and hospitals both public and private. So that the budget can serve as a control, when compiling the budget should be noted that the parties involved in preparing the budget. One is that managers are directly responsible for managing performanc in a public or private organizations. The sampling method used was purposive sampling. In this study, sample criteria are the managers who are at level two in their respective institusions. In the 70 private sector organizations and the public sector is 50. from the results of this study concluded that there are significant relationships between participation publicness in budget making and managing performanc.Key Word: publicness, participation, and managerial performanc